Med trgom in državo - Rončević, Borut (Teorija in praksa, 1999)
ABSTRACT: Numerous authors are searching for answers to the questions connected with relations between the market and the state, particularly in view of high unemployment and the crisis of the welfare (social) state in countries outside the Anglo-Saxon circle. The debate which assumes a competitive relationship between the two spheres is, in various dimensions, unproductive. For this reason the author presents some of the characteristics of a novel approach which attributes more significance to the intermediary sphere. He warns about the poor understanding of the sphere, the confusion related to its naming and the problems ensuing from this. A deeper understanding of the intermediary sphere would fortify its potentials for generating collective goods, therefore the author tries to form at least a rough frame to create a definition of this sphere. In conclusion, various modes of placement of the intermediary sphere among other spheres generating collective goods, are presented.
Keywords: brezposelnost; unemployment; blaginja; socialna politika; ekonomska politika; neprofitni sektor